Temperature-Dependent Gene Expression in Yersinia ruckeri: Tracking Specific Genes by Bioluminescence During in Vivo Colonization - Mendez, Jessica; Cascales, Desirée; Garcia-Torrico, Ana I.; Guijarro, Jose A. (Frontiers in Microbiology, 2018)
Yersinia ruckeri is a bacterium causing fish infection processes at temperatures below the optimum for growth. A derivative Tn5 transposon was used to construct a library of Y. ruckeri mutants with transcriptional fusions between the interrupted genes and the promoterless luxCDABE and lacZY operons. In vitro analysis of β-galactosidase activity allowed the identification of 168 clones having higher expression at 18ºC than at 28ºC. Among the interrupted genes a SAM-dependent methyltransferase, a diguanylated cyclase, three genes involved in legionaminic acid synthesis and three transcriptional regulators were defined. In order to determine, via bioluminescence emission, the in vivo expression of some of these genes, two of the selected mutants were studied. In one of them, the acrR gene coding a repressor involved in regulation of the AcrAB-TolC expulsion pump was interrupted. This mutant was found to be highly resistant to compounds such as chloramphenicol, tetracycline and ciprofloxacin. Although acrR mutation was not related to virulence in Y. ruckeri, this mutant was useful to analyse acrR expression in fish tissues in vivo. The other gene studied was osmY which is activated under osmotic stress and is involved in virulence. In this case, complemented mutant was used for experiments with fish. In vivo analysis of bioluminescence emission by these two strains showed higher values for acrR in gut, liver and adipose tissue, whereas osmY showed higher luminescence in gut and, at the end of the infection process, in muscle tissue. Similar results were obtained in ex vivo assays using rainbow trout tissues. The results indicated that this kind of approach was useful for the identification of genes related to virulence in Y. ruckeri and also for the in vivo and in vitro studies of each of the selected genes.